PENGARUH KERJASAMA TIM, KOMUNIKASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Redo, Julius; Haris, Abdul; Nursito, Sarwono (FAKULTAS EKONOMI DAN PSIKOLOGI UNWIDHA KLATEN, 2024)
Performance is an effort made by an employee to carry out a responsibility given by the company. Performance is a serious concern to achieve company success because without its presence the company will experience difficulty in achieving the desired targets. This research aims to examine the influence of teamwork, communication and work discipline on performance. The sample consisted of 81 employees from one company in Klaten Regency, Central Java, Indonesia. The method used is a quantitative approach by distributing questionnaires to respondents. The research instrument was tested using validity and reliability tests. Next, the collected data was analyzed using multiple linear regression tests using SPSS 25. The research findings showed that teamwork had a positive but not significant effect on performance. Meanwhile, communication and work discipline have a positive and significant effect on employee performance.